A family-specific linkage analysis of blood lipid response to fenofibrate in the Genetics of Lipid Lowering Drug and Diet Network. Issue 10 (October 2015) - Hidalgo, Bertha; Aslibekyan, Stella; Wiener, Howard W.; Irvin, Marguerite R.; Straka, Robert J.; Borecki, Ingrid B.; Tiwari, Hemant K.; Tsai, Michael Y.; Hopkins, Paul N.; Ordovas, Jose M.; Arnett, Donna K.
<x xml:space="preserve">Abstract</x> Cost-effective identification of novel pharmacogenetic variants remains a pressing need in the field. Using data from the Genetics of Lipid Lowering Drugs and Diet Network, we identified genomic regions of relevance to fenofibrate response in a sample of 173 families. Our approach included a multipoint linkage scan, followed by selection of the families showing evidence of linkage. We identified a strong signal for changes in LDL-cholesterol (LDL-C) on chromosome 7 (peak logarithm of odds score=4.76) in the full sample (n=821). The signal for LDL-C response remained even after adjusting for baseline LDL-C. Restricting analyses only to the families contributing to the linkage signal for LDL-C (N=19), we observed a peak logarithm of odds score of 5.17 for chromosome 7. Two genes under this peak (ABCB4 and CD36) were of biological interest. These results suggest that linked family analyses might be a useful approach to gene discovery in the presence of a complex (e.g. multigenic) phenotype.